Negative symptoms at the prodromal stage of schizophrenia at a young age (current problems of diagnostics and treatment) - M. A. Omelchenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The review highlights the problem of early diagnostics of schizophrenia, trying to identify specific markers at the prodromal stage, before the appearance of full clinical symptoms. One of these markers may be negative symptoms, the core symptoms of schizophrenia. On the one hand, they can be considered as predictors of psychosis, and on the other hand, may indicate poor outcomes with a significant decrease of functioning. The report reflects the current concepts of the pathogenesis of negative symptoms, methods of diagnostics and promising directions of therapy.